The Effect of Motivation, Work Environment and Competence on Employee Performance with Work Discipline as a VariableIntervening with Technical Service EmployeesPT PLN (Persero) ULP Pangkalan Susu - Restu Eka Putra; Mesra B (CV. Doki Course and Training, 2026)
This study aims to assess how motivation, working conditions, and skills influence employee performance, with work discipline as a mediator, among engineering service staff at PT PLN (Persero) ULP Pangkalan Susu. A quantitative method was used, incorporating survey techniques. This study covered all engineering service staff, and 76 participants were selected using a saturated sampling method. Information was collected through a questionnaire and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results of the study indicate that work discipline has a positive and significant impact on employee performance. It was found that both motivation and skills positively and significantly influence work discipline, while skills also have a positive and significant direct influence on employee performance. On the other hand, the work environment does not show a significant influence on work discipline or employee performance. In addition, work discipline acts as a mediator for the influence of motivation and skills on employee performance, but does not mediate the influence of the work environment on performance. These results indicate that to improve employee performance at PT PLN (Persero) ULP Pangkalan Susu, efforts must prioritize improving employee discipline, motivation, and skills to achieve the best performance improvement.